The Gayonese Culture of Marriage System: The Islamic Law Perspective - Nurdin, Ridwan; Yusuf, Muhamad; Natasya, Syarifah Sharah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
This research explores the Gayonese culture of marriage through an analytical view of the Islamic law. There has been a shift in marriage system in the Gayonese society, in which the Juelen and the Angkap, the two formerly known systems shifted to Kuso Kini. This is an empirical research using the law historical approach to allow the author restropectively explore the construction of law and its shift from time to time. The data was gathered through an in-depth analysis of the literature and semi-structured interviews of the community leaders. The findings suggest that marriage systems are shifting and the Gayonese communities do not problematize this transformation. In fact, they are not in the position to force their children to adopt both the Juelen and the Angkap marriage system. This is so, since most communities in the present times prefer Kuso Kini marriage system to the other two. The Kuso Kini marriage system gives freedom for spouses to decide where they should stay, either with their parents or find their own living. This shift in marriage system is the result of cultural intermingled, in which some non-Gayonese migrated to the Gayonese Island and brought with them their own cultural values. The same is true to the Gayonese communities migrating to places beyond the Gayonese Island. It is therefore believed that a shift in marriage system is a must as the world today allow people across different cultural values to integrate with each other. The integration for sure gives changes to a certain cultural value. However, changes in cultural practices do not result in cultural-religious clashes. In fact, it is expected that the changes contribute to the family resilience and the marriage cultural system, the Kuso Kini, prevails.